Antiretroviral therapy initiated soon after HIV diagnosis as standard care: potential to save lives? - Simon P Johnstone-Robertson (Dove Medical Press, 2011)
Simon P Johnstone-Robertson, John Hargrove, Brian G WilliamsSouth African Centre for Epidemiological Modelling and Analysis, DST/NRF Centre of Excellence in Epidemiological Modelling and Analysis, Stellenbosch, South AfricaAbstract: In 2008, an estimated 33.4 million people were infected with human immunodeficiency virus (HIV) and ~4 million people were receiving antiretroviral therapy (ART). However, in 2007, an estimated 6.7 million people were in need of ART under the current World Health Organization guidelines, and 2.7 million more people became infected with HIV. Most of those not currently eligible for ART will become eligible within the next decade, making the current treatment strategy unsustainable. The development of cheaper, less toxic, and more potent antiretrovirals over the past decade has made it possible to consider novel strategies of arresting the HIV/AIDS epidemic. Evidence is growing that ART can be used to prevent HIV transmission and that earlier initiation of treatment is beneficial for those infected with HIV. A mathematical model predicts that by testing whole communities annually and treating all who are infected immediately, up to 7.2 million AIDS-related deaths could be prevented in the next 40 years, long-term funding required to fight the HIV epidemic could be reduced, and, most importantly, control of the HIV/AIDS epidemic could be regained within 1–2 years of full-scale implementation of the strategy. We discuss the development of the concept of ART for the prevention of HIV transmission and the modeled impact that a test-and-treat strategy could have on the HIV epidemic, and consequently argue that a field trial should be carried out to confirm model parameters, highlight any practical problems, and test the model’s predictions.Keywords: human immunodeficiency virus (HIV), test-and-treat, mathematical model, transmission, prevention, elimination